2000
DOI: 10.1590/s1516-89132000000300007
|View full text |Cite
|
Sign up to set email alerts
|

Zooplankton community composition and some limnological aspects of an oxbow lake of the Paraopeba River, São Francisco River Basin, Minas Gerais, Brazil

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…A similar pattern has been recorded in the aquatic systems of white-(77%) and black-water (40%) rivers in the Amazon basin (Table 3), as well as other systems (see Green, 1972;Dumont, 1983;Neves et al, 2003;Paggi and José de Paggi, 1990;Sampaio and López, 2000).…”
Section: Discussionsupporting
confidence: 79%
“…A similar pattern has been recorded in the aquatic systems of white-(77%) and black-water (40%) rivers in the Amazon basin (Table 3), as well as other systems (see Green, 1972;Dumont, 1983;Neves et al, 2003;Paggi and José de Paggi, 1990;Sampaio and López, 2000).…”
Section: Discussionsupporting
confidence: 79%
“…Studies carried out in floodplain water regions of the Daugava River, and Gruberts et al (2007) showed an inverse and statistically significant correlation between the water level and the general abundance of zooplankton. Thereafter, Sampaio & López (2000) emphasised the influence of high water levels of the Paraopeba River on the improvement of oxygen level in the floodplain lakes and an increase in the density and biodiversity of the Copepoda and Rotifera structure. Our studies showed that higher water levels favoured occurrence of a higher diversity of crustaceans and protozoans at the cost of a decrease in the rotifer share.…”
Section: Discussionmentioning
confidence: 99%
“…3C). A strong prevalence of one or several species preferring high biogen concentrations, often connected to a decrease in the dissolved oxygen contents, causes an elimination of many more sensitive taxa (Sampaio & López, 2000). An influence of progressive eutrophication of paleopotamic floodplain lakes on depletion of the Crustacea structure has been discussed by many researchers, including Paganelli & Sconfietti (2013) in a Topo lake on the Ticino River (Italy), as well as Illyová (2006) for the floodplain lakes along the Morava River (Slovakia).…”
Section: Discussionmentioning
confidence: 99%
“…In the neotropical region, this genus is relatively poor in species. T. minutus is a common species, restricted to South America, mainly in Brazil (Rocha et al, 1995;Sampaio and López, 2000). T. decipiens also has a wide distribution, and in many places, these two species can occur together.…”
Section: Introductionmentioning
confidence: 99%